2021
DOI: 10.1016/j.celrep.2021.109086
|View full text |Cite|
|
Sign up to set email alerts
|

Broad and potently neutralizing monoclonal antibodies isolated from human survivors of New World hantavirus infection

Abstract: SUMMARY New World hantaviruses (NWHs) are endemic in North and South America and cause hantavirus cardiopulmonary syndrome (HCPS), with a case fatality rate of up to 40%. Knowledge of the natural humoral immune response to NWH infection is limited. Here, we describe human monoclonal antibodies (mAbs) isolated from individuals previously infected with Sin Nombre virus (SNV) or Andes virus (ANDV). Most SNV-reactive antibodies show broad recognition and cross-neutralization of both New and Old World ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 78 publications
(116 reference statements)
2
48
0
Order By: Relevance
“…S9B). Together, these results indicate that many of our nAbs selected for neutralization potency and breadth directly interfere with Gn/Gc-dependent viral membrane fusion, as also observed for previously isolated nAbs ( 26 ), suggesting that they act by targeting one or more steps in the membrane fusion reaction, including Gn:Gc dissociation, and Gc target membrane insertion and homotrimerization.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…S9B). Together, these results indicate that many of our nAbs selected for neutralization potency and breadth directly interfere with Gn/Gc-dependent viral membrane fusion, as also observed for previously isolated nAbs ( 26 ), suggesting that they act by targeting one or more steps in the membrane fusion reaction, including Gn:Gc dissociation, and Gc target membrane insertion and homotrimerization.…”
Section: Resultssupporting
confidence: 81%
“…In addition, two recent studies have isolated spike-specific mAbs from ANDV- and/or SNV-experienced HCPS-convalescent donors and identified several that could protect Syrian hamsters from lethal ANDV challenge ( 26 , 27 ). Most of the protective lead mAbs in these reports recognized and/or neutralized Gn/Gc in a virus-specific manner, and Engdahl and colleagues ( 26 ) described several nAbs isolated from SNV-experienced donors with activity against members of both Old World and New World clades (hereafter, cross-clade activity; see Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most promising candidate vaccines are based on multivalent DNA vaccines containing the M segment of one to four hantaviruses (two of them are in phase I/II clinical trials) [ 30 ]. However, although serologic studies in humans and immunization trials in animals using these multivalent DNA vaccines may have confirmed a certain degree of cross-neutralization across the hantavirus species, this cross-neutralizing activity appears to display high variability, notably depending on the viruses used in the candidate vaccine [ 31 , 32 ].…”
Section: Orthohantaviruses ( Hantaviridae Family): An Example Of the Importance Of The Quaternary Spike Strucmentioning
confidence: 99%
“…Engdahl and colleagues began to decipher the molecular determinants of this variability, providing hints for how to overcome it. Using a panel of 20 mAbs from three donors previously infected with Sin Nombre virus (SNV) and 16 mAbs from one donor previously infected with ANDV, they showed that the variation in the breadth of the humoral response was linked to the different viral glycoproteins targeted by the mAbs: most of the broadly-reactive mAbs recognized Gc whereas the virus-specific mAbs targeted Gn [ 31 ]. This correlation was also observed in murine mAbs derived from B cells of immunized mice [ 22 ].…”
Section: Orthohantaviruses ( Hantaviridae Family): An Example Of the Importance Of The Quaternary Spike Strucmentioning
confidence: 99%
See 1 more Smart Citation